Twelve-month results of the rapid renal sympathetic denervation for resistant hypertension using the OneShotTM ablation system (RAPID) study - Verheye, Stefan; Heilmeier, Britta (EuroIntervention, 2015)
The Official Journal of EuroPCR and the European Association of Percutaneous Cardiovascular Interventions (EAPCI)
published online: December 2014
Gesehen am 09.07.2020